INFLUENCE OF VARIETIES AND TECHNOLOGY UPON THE YIELD OF SEVERAL BARLEY VARIETIES GROWN IN THE SOUTH EASTERN PART OF ROMANIA - Nicoleta OLTENACU; Elena LASCAR; Cecilia NEAGU; Valentina GAVRILA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Barley (Hordeum vulgare), unlike other cereals, is distinguished by a wider geographical spread, being the only cereal that reaches 70 degrees North altitude. Barley provides the human body a wide range of nutrients: vitamins (B1, B2, B3, B6), minerals (selenium, manganese, iron, magnesium, phosphorus, zinc, copper) and dietary fibre. These qualities as well as many others make this crop constantly in the structure of crops. That is why, the research aimed at improving the quality of this plant is constantly evolving. Study of the behaviour in crop was analyzed, under the same technological and land and climate conditions, four varieties of Hanzi, Alora, Amorosa and Finola barley. The research was carried out during the year 2018, in the Southeastern part of the Romanian Plain. After harvest, determinations were made regarding the protein content, hectolitre weight, MMB and efficiency per hectare for each variety. The best efficiency was made by Hanzi variety that exceeded the production of the control variety by 30%.